2021
DOI: 10.33997/j.afs.2021.34.1.011
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Small-Scale Fisheries in Southeast Asia: Impacts and Responses

Abstract: This paper describes the impacts of and responses to COVID-19 of small-scale fisheries in six selected countries in Southeast Asia, including Indonesia, Malaysia, Myanmar, Philippines, Thailand, and Vietnam. The paper used a structured case study approach to analyse the impacts and responses and relied heavily on existing reports and data sources in each country. The pandemic has further revealed the vulnerability of small-scale fishing households in the region. Given the few assets of fisher households, their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 23 publications
2
51
0
Order By: Relevance
“…Results of the survey to recreational fishers and of the expert consultation showed that it is expected that global fish stocks could benefit from the reduction of the impacts of commercial fisheries during the COVID-19 pandemic, in line with what was found in recent studies (e.g., Kemp et al, 2020;Coll et al, 2021;Ferrer et al, 2021;White et al, 2021a). Whether reductions of recreational fishing effort will accrue similar benefits is less clear for recreational fishers, especially in the case of older and more educated fishers.…”
Section: Global Importancesupporting
confidence: 55%
“…Results of the survey to recreational fishers and of the expert consultation showed that it is expected that global fish stocks could benefit from the reduction of the impacts of commercial fisheries during the COVID-19 pandemic, in line with what was found in recent studies (e.g., Kemp et al, 2020;Coll et al, 2021;Ferrer et al, 2021;White et al, 2021a). Whether reductions of recreational fishing effort will accrue similar benefits is less clear for recreational fishers, especially in the case of older and more educated fishers.…”
Section: Global Importancesupporting
confidence: 55%
“…The effects of COVID-19 on food systems, and the producers and consumers of aquatic foods (Béné, 2020;Belton et al, 2020;FAO et al, 2020;Ferrer et al, 2021), are a particularly stark example of the importance of increasing understanding of, and planning for, external shocks on food systems, including efforts to understand and build resilience of food systems in ways that reduce future vulnerabilities.…”
Section: Emerging Challenges For Food Systemsmentioning
confidence: 99%
“…Fishery activities have been affected by COVID-19 in terms of fishing efforts, landings, and marketing, thus directly affecting the livelihood of fishers. The inability to fish and reduced demand are major factors affecting the fishery industry, especially the smallscale fisheries in Southeast Asia [69]. The decrease of activities along the production and marketing chains such as suppliers (fishers), traders, processors, transporters, consumers, and financiers resulted in the collapse of the fishery industry.…”
Section: Covid-19 On Fishery and Aquaculture Industriesmentioning
confidence: 99%
“…The COVID-19 pandemic has significantly reduced fishing pressure, providing opportunities for threatened species to recover. Many researchers from United Kingdom [71], Mediterranean [12], Indonesia [69,72], India [34], Africa [73,74], North America [75], and Bangladesh [76] reported that reduced fishing pressure resulted in an increase of wild stocks in inland and marine waters. Even reef fish densities increased substantially due to the COVID-19 lockdown [34].…”
Section: Covid-19 and Fisheries Industrymentioning
confidence: 99%
See 1 more Smart Citation